逆三角関数の逆双曲線関数の対数表示

逆三角関数の対数表示

(1)

\[ \sin^{\circ}z=-i\log\left(iz\pm\sqrt{1-z^{2}}\right) \]

(2)

\[ \cos^{\circ}z=-i\log\left(z\pm i\sqrt{1-z^{2}}\right) \]

(3)

\[ \tan^{\circ}z=-i\log\left(\pm\sqrt{\frac{i-z}{i+z}}\right) \]

(4)

\[ \sin^{-1,\circ}z=-i\log\left(\frac{i}{z}\pm\sqrt{1-\frac{1}{z^{2}}}\right) \]

(5)

\[ \cos^{-1,\circ}z=-i\log\left(\frac{1}{z}\pm i\sqrt{1-\frac{1}{z^{2}}}\right) \]

(6)

\[ \tan^{-1,\circ}z=-i\log\left(\pm\sqrt{\frac{z+i}{z-i}}\right) \]

(1)

\begin{align*} w & =\sin z\\ & =\frac{e^{iz}-e^{-iz}}{2i} \end{align*}

より、

\[ \left(e^{iz}\right)^{2}-2iw\left(e^{iz}\right)-1=0 \]

\(e^{iz}\)について解くと、

\[ e^{iz}=iw\pm\sqrt{1-w^{2}} \]

となるので、

\begin{align*} \sin^{\circ}w & =z\\ & =-i\log\left(iw\pm\sqrt{1-w^{2}}\right) \end{align*}

(2)

\begin{align*} w & =\cos z\\ & =\frac{e^{iz}+e^{-iz}}{2} \end{align*}

より、

\[ \left(e^{iz}\right)^{2}-2w\left(e^{iz}\right)+1=0 \]

\(e^{iz}\)について解くと、

\[ e^{iz}=w\pm i\sqrt{1-w^{2}} \]

となるので、

\begin{align*} \cos^{\circ}w & =z\\ & =-i\log\left(w\pm i\sqrt{1-w^{2}}\right) \end{align*}

(3)

\begin{align*} w & =\tan z\\ & =-i\frac{e^{iz}-e^{-iz}}{e^{iz}+e^{-iz}} \end{align*}

より、

\[ \left(w+i\right)\left(e^{iz}\right)^{2}+\left(w-i\right)=0 \]

\(e^{iz}\)について解くと、

\[ e^{iz}=\pm\sqrt{\frac{i-w}{i+w}} \]

となるので、

\begin{align*} \tan^{\circ}w & =z\\ & =-i\log\left(\pm\sqrt{\frac{i-w}{i+w}}\right) \end{align*}

(4)

\begin{align*} w & =\sin^{-1}z\\ & =\frac{2i}{e^{iz}-e^{-iz}} \end{align*}

より、

\[ w\left(e^{iz}\right)^{2}-2i\left(e^{iz}\right)-w=0 \]

\(e^{iz}\)について解くと、

\[ e^{iz}=\frac{i\pm\sqrt{w^{2}-1}}{w} \]

となるので、

\begin{align*} \sin^{-1,\circ}w & =z\\ & =-i\log\left(\frac{i}{w}\pm\sqrt{1-\frac{1}{w^{2}}}\right) \end{align*}

(5)

\begin{align*} w & =\cos^{-1}z\\ & =\frac{2}{e^{iz}+e^{-iz}} \end{align*}

より、

\[ w\left(e^{iz}\right)^{2}-2\left(e^{iz}\right)+w=0 \]

\(e^{iz}\)について解くと、

\[ e^{iz}=\frac{1\pm\sqrt{1-w^{2}}}{w} \]

となるので、

\begin{align*} \cos^{-1,\circ}w & =z\\ & =-i\log\left(\frac{1}{w}\pm i\sqrt{1-\frac{1}{w^{2}}}\right) \end{align*}

(6)

\begin{align*} w & =\tan^{-1}z\\ & =i\frac{e^{iz}+e^{-iz}}{e^{iz}-e^{-iz}} \end{align*}

より、

\[ \left(w-i\right)\left(e^{iz}\right)^{2}-\left(w+i\right)=0 \]

\(e^{iz}\)について解くと、

\[ e^{iz}=\pm\sqrt{\frac{w+i}{w-i}} \]

となるので、

\begin{align*} \tan^{-1,\circ}w & =z\\ & =-i\log\left(\pm\sqrt{\frac{w+i}{w-i}}\right) \end{align*}

逆双曲線関数の対数表示

(1)

\[ \sinh^{\circ}w=\log\left(w\pm\sqrt{w^{2}+1}\right) \]

(2)

\[ \cosh^{\circ}w=\log\left(w\pm\sqrt{w^{2}-1}\right) \]

(3)

\[ \tanh^{\circ}w=\log\left(\pm\sqrt{\frac{1+w}{1-w}}\right) \]

(4)

\[ \sinh^{-1,\circ}w=\log\left(\frac{1}{w}\pm\sqrt{\frac{1}{w^{2}}+1}\right) \]

(5)

\[ \cosh^{-1,\circ}w=\log\left(\frac{1}{w}\pm\sqrt{\frac{1}{w^{2}}-1}\right) \]

(6)

\[ \tanh^{-1,\circ}w=\log\left(\pm\sqrt{\frac{w+1}{w-1}}\right) \]

(1)

\begin{align*} w & =\sinh z\\ & =\frac{e^{z}-e^{-z}}{2} \end{align*}

より、

\[ \left(e^{z}\right)^{2}-2w\left(e^{z}\right)-1=0 \]

\(e^{z}\)について解くと、

\[ e^{z}=w\pm\sqrt{w^{2}+1} \]

となるので、

\begin{align*} \sinh^{\circ}w & =z\\ & =\log\left(w\pm\sqrt{w^{2}+1}\right) \end{align*}

(2)

\begin{align*} w & =\cosh z\\ & =\frac{e^{z}+e^{-z}}{2} \end{align*}

より、

\[ \left(e^{z}\right)^{2}-2w\left(e^{z}\right)+1=0 \]

\(e^{iz}\)について解くと、

\[ e^{z}=w\pm\sqrt{w^{2}-1} \]

となるので、

\begin{align*} \cosh^{\circ}w & =z\\ & =\log\left(w\pm\sqrt{w^{2}-1}\right) \end{align*}

(3)

\begin{align*} w & =\tanh z\\ & =\frac{e^{z}-e^{-z}}{e^{z}+e^{-z}} \end{align*}

より、

\[ \left(w-1\right)\left(e^{z}\right)^{2}+\left(w+1\right)=0 \]

\(e^{z}\)について解くと、

\[ e^{z}=\pm\sqrt{\frac{1+w}{1-w}} \]

となるので、

\begin{align*} \tanh^{\circ}w & =z\\ & =\log\left(\pm\sqrt{\frac{1+w}{1-w}}\right) \end{align*}

(4)

\begin{align*} w & =\sinh^{-1}z\\ & =\frac{2}{e^{z}-e^{-z}} \end{align*}

より、

\[ w\left(e^{z}\right)^{2}-2\left(e^{z}\right)-w=0 \]

\(e^{z}\)について解くと、

\[ e^{z}=\frac{1\pm\sqrt{1+w^{2}}}{w} \]

となるので、

\begin{align*} \sinh^{-1,\circ}w & =z\\ & =\log\left(\frac{1}{w}\pm\sqrt{\frac{1}{w^{2}}+1}\right) \end{align*}

(5)

\begin{align*} w & =\cosh^{-1}z\\ & =\frac{2}{e^{z}+e^{-z}} \end{align*}

より、

\[ w\left(e^{z}\right)^{2}-2\left(e^{z}\right)+w=0 \]

\(e^{z}\)について解くと、

\[ e^{z}=\frac{1\pm\sqrt{1-w^{2}}}{w} \]

となるので、

\begin{align*} \cosh^{-1,\circ}w & =z\\ & =\log\left(\frac{1}{w}\pm\sqrt{\frac{1}{w^{2}}-1}\right) \end{align*}

(6)

\begin{align*} w & =\tanh^{-1}z\\ & =\frac{e^{z}+e^{-z}}{e^{z}-e^{-z}} \end{align*}

より、

\[ \left(w-1\right)\left(e^{iz}\right)^{2}-\left(w+1\right)=0 \]

\(e^{z}\)について解くと、

\[ e^{iz}=\pm\sqrt{\frac{w+1}{w-1}} \]

となるので、

\begin{align*} \tanh^{-1,\circ}w & =z\\ & =\log\left(\pm\sqrt{\frac{w+1}{w-1}}\right) \end{align*}

ページ情報

タイトル

逆三角関数の逆双曲線関数の対数表示

URL

https://www.nomuramath.com/rr3au8qa/

SNSボタン